Analisa pemakaian energi listrik dan cop pada AC split 900 watt menggunakan refrigeran hidrokarbon MC-22 dan R-22 - Harsono .; Bambang Santosa (Badan Kerja Sama Teknik Mesin Indonesia, 2017)
To know the efficiency of work one AC equipment needs to know electricenergy consumption , the effect of performance and those obtained fromrefrigeration and ( cop ) .Most air conditioning system synthetic / ac wearinga refrigerant .The use of synthetic a refrigerant were forbidden to thegovernment of the republic of indonesia no. 1 according to the decisionmenperindag 79/mpp /kep/12 /2002 because they include ozone as depletingsubstance ( ods ) , That is a substance that can result in damage to the ozonelayer , in addition to the still have the potential as the substance which cancause the effects of global warming because it has global warming potentialgwp ( ) that is significant .On this thesis a refrigerant kept on a constantreview the use of environmentally friendly , namely a refrigerant musicoolhydrocarbon / 22 r-22 mc-22 as a substitute for .A refrigerant mc-22compatible with air conditioner use r-22 components .From the research acsplit by using r-22 , electric power usage 726 watts , the effect ofrefrigeration 149.07 kj / kg and cop 4.9 .Then maybe you an use mc-22 653wat electricity power usage.